2013
DOI: 10.1055/s-0037-1607087
|View full text |Cite
|
Sign up to set email alerts
|

Resección artroscópica del polo distal del escafoides en la artrosis escafo-trapecio-trapezoidea

Abstract: La artrosis escafo-trapecio-trapezoidea se asocia frecuentemente a una inestabilidad carpiana. En dichas ocasiones el tratamiento quirúrgico abierto mediante la resección simple del polo distal puede ocasionar un colapso carpiano. El uso de la artroscopia para la resección del polo distal del escafoides permite, no solo la resección del polo distal a través de un abordaje mínimamente invasivo, sino también la evaluación y posible tratamiento de inestabilidades carpianas asociadas. En el presente trabajo se det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Other authors 6,22,[28][29][30] have reported the relationship of STT-OA with ligament injury and SL dissociation. Wadhwani et al 28 assessed 618 radiographs of patients with wrist pain, 43 (7%) of which presented SL ligament injury, with SL space widening greater than 4 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other authors 6,22,[28][29][30] have reported the relationship of STT-OA with ligament injury and SL dissociation. Wadhwani et al 28 assessed 618 radiographs of patients with wrist pain, 43 (7%) of which presented SL ligament injury, with SL space widening greater than 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Other procedures have also been proposed in an attempt to improve STT joint motion by reducing the local inflammatory process created by OA and the overloading of adjacent joints. 3,10,30 Isolated arthroscopic debridement with synovectomy and osteophyte resection has demonstrated good results in the short term, with 90% of satisfaction in 3 years, but its long-term evolution and the use in advanced stages of the disease are not known. 41 Another treatment option, as proposed by Garcia-Elias et al, [42][43][44] is the resection of the distal pole of the scaphoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations